The Structure of an Arctic Microeconomy: The Traditional Sector in Community Economic Development - Quigley, N.C.; McBride, N.J. (ARCTIC, 1987)
Data collected during 1984-85 are used to describe income and expenditure flows in Sanikiluaq, N.W.T. (the principal settlement on the Belcher Islands in Hudson Bay) and to construct a model that distinguishes between the traditional and modern sectors, as well as between the cash and non-cash (traditional food) sectors, of the community economy. When judged by imputed value, the harvest from the traditional sector is the single largest component of community income, but this activity necessarily has close links with the cash sector. Expansion of activity in the traditional food sector is hampered by the necessity of purchasing equipment and fuel in advance, and because there are few opportunities to sell the output of this sector, the problem cannot be solved solely by availability of credit. Because the cash income from jobs in the business and government sectors of the economy are concentrated in a small number of households, receipts from carving and social assistance play a crucial role in relieving the cash constraint on households operating primarily in the country food sector. We conclude that policies designed to ensure the vitality of the country food sector, by removing cash constraints on participation and investigating the sustainability of future harvesting levels, should be an integral part of community development strategies.Key words: Sanikiluaq, Inuit, community economic structure, traditional food sector, income and expenditure, economic development strategies On se sert de données recueillies en 1984-85 pour décrire les flux des revenus et dépenses à Sanikiluaq, le village le plus important des îles Belcher dans la baie d'Hudson (T. du N.-O.), et pour construire un modèle qui distingue entre les secteurs traditionnels et modernes, ainsi qu'entre ceux des liquidités et ceux non monétaires (alimentation traditionnelle) de l'économie de la communauté. Si l'on s'en remet à la valeur imputée, la composante la plus importante des revenus de la communauté est constituée de loin par le produit de ...